2019
DOI: 10.18632/aging.102425
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin specific peptidase 5 promotes ovarian cancer cell proliferation through deubiquitinating HDAC2

Abstract: Globally, epithelial ovarian cancer (EOC) is the most common gynecological malignancy with poor prognosis. The expression and oncogenic roles of ubiquitin specific peptidase 5 (USP5) have been reported in several cancers except EOC. In the current study, USP5 amplification was highly prevalent in patients with EOC and associated with higher mRNA expression of USP5. USP5 amplification and overexpression was positively correlated with poor prognosis of patients of ovarian serous carcinomas. Disruption of USP5 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 40 publications
3
25
0
Order By: Relevance
“…[26][27][28] Apart from them, a growing body of evidence has demonstrated the tumor-promoting role of USP5 in different cancer types. 8,10,11,[13][14][15] And in this study, we found that it was also the case in UCEC. When USP5 was knocked down, cell viability was significantly impeded accompanied with blockade of cell cycle transition and induction of apoptosis.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…[26][27][28] Apart from them, a growing body of evidence has demonstrated the tumor-promoting role of USP5 in different cancer types. 8,10,11,[13][14][15] And in this study, we found that it was also the case in UCEC. When USP5 was knocked down, cell viability was significantly impeded accompanied with blockade of cell cycle transition and induction of apoptosis.…”
Section: Discussionsupporting
confidence: 59%
“…The Decease of USP5 Causes Cell Cycle Arrest and Apoptosis of UCEC Cells USP5 was shown to modulate cell cycle progression in pancreatic cancer and ovarian cancer. 14,15 To reveal the mechanisms underlying the repression of cell proliferation, we analyzed cell cycle distribution of UCEC cells after USP5 knockdown. We observed significant accumulations of Hec-1-B cells in G0/G1-phase transfected with USP5 siRNAs compared to control cells, and meanwhile obvious reductions in S-phase and G2/M-phase (Figure 4A).…”
Section: Usp5 Downregulation Impairs Ucec Cell Proliferationmentioning
confidence: 99%
“…USP5 is one of the important members of USP family. USP5 have been reported as an oncoprotein in diverse cancers including myeloma 4 , non-small cell lung cancer 5 , hepatocellular carcinoma 6 , colorectal cancer 7 , ovarian cancer 8 and pancreatic cancer 9 . USP5 have been studied in the development of pancreatic cancer 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Along with the decrease in b-catenin expression by knocking down USP5, it is suggested that these beneficial effects of USP5 are involved in the upregulation of Wnt/b-catenin signaling. It has been reported that USP5 promotes tumor proliferation and tumorigenesis through the deubiquitination of histone deacetylase 2 (HDAC2) (Du et al, 2019) and b-catenin (Ma et al, 2018). Meanwhile, HDAC2, a histone deacetylase, decreases GSK-3b protein (Wang et al, 2016), likely by deacetylating its histone proteins, hence impairing its gene transcription.…”
Section: Discussionmentioning
confidence: 99%